Pendidikan Nilai Akidah dan Akhlak kepada Anak Sejak Dini - Sawaliyah, Yuniarsih (Darul Yasin Al Sys, 2024)
This research aims to find out the values of religious education that need to be taught from an early age to children, to find out the values of moral education that need to be taught from an early age to children. This research is descriptive analysis, namely an effort to collect and compile data, then efforts are also made to analyze and interpret these data, so that it can be described in detail and in depth about the values of faith and morals. As a result of the research, it can be concluded that the values of faith and morals can be used as lessons and sources of good values in children from an early age. where each value comes from the Qur'an and Hadith. With an educational style that is able to be understood and grasped by children so that the values of faith and morals become educational values that must be instilled in children from an early age so that they will always be a guide in the future, one of which is in determining their daily attitudes so that they become good habits that are sustainable in the future.